Assessment of Dynamic Effects of Wave Loads in Fatigue Analysis for Fixed Steel Offshore Structures - Dinh Quang Cuong; Bui The Anh (Salehan Institute of Higher Education, 2023)
This paper presents an algorithm and develops a formula to evaluate the dynamic effect of wave loading on fixed steel offshore structures (jacket structures) through the fatigue damage ratio. Applying the algorithm and formula proposed in this paper to evaluate the dynamic effect of wave loads in fatigue analysis for 03 Jacket structures built at increasing water depth under one specific marine condition and provide specific recommendations on the limits of application of quasi-static and dynamic methods in the fatigue analysis of the jacket structures. This research is really necessary because currently, the current standards (API, DnV) only stop at evaluating the dynamic effects of wave loads acting on the Jacket structure in the strength analysis. These standards propose a limit for quasi-static or dynamic analysis based on the